The Effects of Immunosuppression on the Lung Microbiome and Metabolites in Rats - Dong, Huiwei; Tan, Rong; Chen, Zhengshan; Wang, Lifang; Song, Yuanyuan; Jin, Min; Yin, Jing; Li, Haibei; Li, Junwen; Yang, Dong (Frontiers in Microbiology, 2022)
Immunosuppressed patients are more likely to suffer from pneumonia, especially Streptococcus and Enterobacter pneumonia. Studies have demonstrated the existence of a complex and dynamic microbiota on the surface of human respiratory epithelial cells, both in healthy and diseased states. However, it is not clear whether the pneumonia in immunosuppressed patients is caused by inhaled oropharyngeal pathogens or abnormal proliferation of pulmonary proteobacteria. In this study, immunosuppressed model was made by intraperitoneal injection of cyclophosphamide and oropharyngeal saliva aspiration was simulated by oral and pharyngeal tracheal instillation of sterilized phosphate buffered saline (PBS). Furthermore, the effects of immunosuppression on the lung microbial community and its metabolism were investigated using 16S rRNA gene sequencing and liquid chromatography-mass spectrometry (LC-MS) metabolomics analysis. The 16S rRNA gene sequencing results showed that immunosuppression alone did not change the composition of pulmonary bacteria. Moreover, although the bacteria brought by sterilized PBS from oropharynx to lower respiratory tract changed the composition of the microflora in healthy and immunosuppressed rats, the change in the latter was more obvious. Metabolomic analysis revealed that the levels of pulmonary metabolites were disturbed in the immunosuppressed rats. The altered lung microbiota, including Streptococcaceae and Enterobacteriaceae, showed significant positive correlations with pulmonary metabolites. Our study suggested that the source of the pathogens of pneumonia in immunosuppressed rats was via inhalation and explored the relationship between lung microbiome and metabolites in immunosuppressed rats. Our results provide the basis for the development of prevention and treatment strategies for pneumonia.